RealTime Mass Sensing by Nanomechanical Resonatorsin Fluid - HEGNER, MARTIN (My University, 2004)
We have developed a sensitive method for real-time mass sensing in a fluid using a microfabricated array of nanomechanical cantilevers actuated at their resonance frequencies. The sensor platform consists of a streptavidin layer immobilised onto gold-coated cantilevers and interacts with biotin-labeled latex beads. The addition of mass involved with this process decreased the resonance frequency. By monitoring frequency spectra of higher harmonics we measured a mass sensitivity of 3.3 Hz/pg. Our data demonstrate that the sensitivity can be increased by operating the cantilever at higher harmonics.
PUBLISHED
Keywords: Physics